Complications secondary to a retained metallic intraocular foreign body (Ukrainian Journal of Ophthalmology, 2025)
Background: Delays in the diagnosis of a ferrous intraocular foreign body (IOFB) have been shown to result in ocular sinerosis and subsequent loss of visual function.Purpose: To report a case of a missed ferrous IOFB with subsequent apparent ocular siderosis, visual loss and severe complications.Material and Methods: Visual acuity assessment and comprehensive eye examination were performed, and an X-ray of the eye and orbit taken.Results: A 25 year-old male patient had a history of hammer-and-chisel (metal-related) injury to the right eye and was treated conservatively. A year after the traumatic event, the eye had phacoemulsification with intraocular lens (IOL) implantation at a local clinic. Two years thereafter, the patient presented to the Filatov institute, and was diagnosed with grade 3 ocular siderosis, artifakia and rhegmatogenous retinal detachment OD.   During pars plana vitrectomy, a preretinal IOFB was found and removed. Four months thereafter, the patient was re-hospitalized and received a repeat pars plana vitrectomy and 5700-cSt silicone oil tamponade of the vitreous cavity for retinal re-detachment OD. At discharge, the ophthalmoscopy and ultrasound examination showed a re-attached retina.Conclusion: The reported case of missed IOFB highlights the importance of early diagnosis and removal of IOFB to prevent siderosis and subsequent serious complications.
Keywords: intraocular foreign body; siderosis; vitrectomy